2018
DOI: 10.1186/s13036-018-0129-0
|View full text |Cite
|
Sign up to set email alerts
|

CD24 identifies nucleus pulposus progenitors/notochordal cells for disc regeneration

Abstract: BackgroundCell-based therapy by transplantation of nucleus pulposus (NP) progenitor/notochordal cells has been proposed as a promising way to halt and reverse the progression of disc degeneration. Although some studies have provided a broad panel of potential markers associated with the phenotype of notochordal cells, suitability of these markers for isolation of notochordal cells for the treatment of disc degeneration is unclear.ResultsHere, we found that the number of CD24-positive NP cells significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…HIF-1α, a key transcription factor in hypoxic condition, plays an important role in promoting cell survival, matrix synthesis, and regulating energy metabolism, in the disc under hypoxic condition (Choi et al, 2015;Risbud et al, 2006). Through HIF-1α, hypoxia controls a host of factors, such as SDC4 (Fujita et al, 2014), CA12 (Chen et al, 2016) and CD24 (Liu et al, 2018), which contribute to maintain homeostasis of NP and protect against degeneration in hypoxic condition of the disc. Although there was no evidence to conclude that HIF-1α could enhance the expression of CD44 in NPCs, several researchers have shown that expression of CD44 correlated with hypoxia-induced gene signatures in tumours.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α, a key transcription factor in hypoxic condition, plays an important role in promoting cell survival, matrix synthesis, and regulating energy metabolism, in the disc under hypoxic condition (Choi et al, 2015;Risbud et al, 2006). Through HIF-1α, hypoxia controls a host of factors, such as SDC4 (Fujita et al, 2014), CA12 (Chen et al, 2016) and CD24 (Liu et al, 2018), which contribute to maintain homeostasis of NP and protect against degeneration in hypoxic condition of the disc. Although there was no evidence to conclude that HIF-1α could enhance the expression of CD44 in NPCs, several researchers have shown that expression of CD44 correlated with hypoxia-induced gene signatures in tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot was performed as previously described 22 . The blots were incubated with antibodies against cleaved-caspase-3 (ab13847, Abcam, USA), cleavedcaspase-9 (ab202068, Abcam, USA), Bax (ab32503, Abcam, USA), Bcl-2 (ab59348, Abcam, USA), cytochrome-c (ab133504, Abcam, USA), phospho-JNK (5599, CST, USA), JNK (9252, CST, USA), LC3B (ab48394, Abcam, USA), Beclin-1 (ab207612, Abcam, USA), P62 (ab109012, Abcam, USA) or Atg-5 (ab108327, Abcam, USA) at 4°C overnight.…”
Section: Western Blotmentioning
confidence: 99%
“…It should be noted that CD24 was detected to express in NPCs, and CD24+ NPCs decreased with IVDD severity 71 . Previously, CD24+ NPCs were identified as progenitors in NP 72 . In humans, the percentage of CD24+NPCs decreased significantly with aging or degeneration, which dropped to less than 10% in elderly adults or severely degenerated discs 73 .…”
Section: Discussionmentioning
confidence: 98%